OPTIMIZING THE IMMOBILIZATION OF BACILLUS SP. F7 WITH CALCIUM ALGINATE IN BIOSURFACTANT PRODUCTION AND BIOSURFACTANT CHARACTERIZATION IN MICROBIAL ENHANCED OIL RECOVERY (MEOR) - Gusning Ati, Aulia
Bacillus sp. F7 is known to produce biosurfactants and has the potential to be applied in the Microbial Enhanced Oil Recovery (MEOR) process. However, high production costs and low yields are the biggest concern when biosurfactant is applied in large-scale industries. One solution that can be done to optimize the production of biosurfactants is to immobilize Bacillus sp. F7 uses calcium alginate matrix. The cell immobilization process can increase the yields of biosurfactants due to the use of high inoculum density and the nature of bacteria that are more stable, resistant to extreme environments, and can live for a longer period of time. Immobilization of cells can also reduce production costs because immobilized cells can be used repeatedly in several production cycles, are not prone to contamination, can be used in relatively longer reactions, and easy to separate in the downstream stage. The immobilization process using calcium alginate has many advantages, such as the manufacturing process is fast, non-toxic, and economical. Besides the optimization of biosurfactant production, the structural characteristics of the biosurfactants produced by Bacillus sp. F7 also needs to be known to maximize the application of biosurfactants. Therefore, this study aims to optimize the process of immobilization of Bacillus sp. F7 with calcium alginate matrix, compared the productivity of immobilized cells with free cells, determined the resistance of alginate gel or beads in several production cycles, and determined the structural characteristics of biosurfactants. In this study, the production of biosurfactants was carried out in a batch system using stone mineral salt solution medium with molasses 2.12% (w/v), urea 0.41% (w/v), and KH2PO4 0.01% (w/v), pH 7.5, temperature of 50 oC and agitation of 150 rpm. The immobilization optimization was carried out using the Response Surface Methodology, Central Composite Design (CCD) method on Design Expert v.11 software. The results showed that the use of 2.5% (w/v) Na-alginate, 3.68% (w/v) CaCl2, and 60 minutes of hardening time would produce optimum beads that could trap bacteria up to 109 CFU/ml after 88 hours of biosurfactant production process. The results of this optimization are then used to immobilize Bacillus sp. F7 with initial number of bacteria in beads 106 and 108 CFU/ml. The immobilized bacteria were compared for their productivity with bacteria that were not immobilized in the production of biosurfactants. The immobilization process of Bacillus sp. F7 can increase the production of biosurfactants compared to free cells. Immobilized bacteria with initial inoculum concentration of 106 and 108 CFU/ml produced the higher dry weight biosurfactants of 0.15 g/l and 0.21 g/l after 78 hours compared to free cells, which was 0.09 g/l after 72 hours. Free and immobilized cells (inoculum concentration 106 and 108 CFU/ml) were able to reduce the oil-water interfacial tension (IFT) with values that were not much different, namely 25.04%, 25.66%, and 25.37%. Cells with an inoculum concentration of 106 CFU/ml were able to maintain the number of bacterial cells better than cells with an initial inoculum concentration of 108 CFU/ml as evidenced by the number of bacteria in the beads after 88 hours of biosurfactant production. Immobilized bacteria (inoculum concentration of 106 CFU/ml) on calcium alginate matrix is tested for resistance as an inoculum used in several production cycles. As a result, immobilized bacteria can be used repeatedly as inoculum for up to 4 production cycles, reduce IFT by 25.15%, and maintain the concentration of bacteria in beads around 106 CFU/ml after the 4th production. The biosurfactant produced by Bacillus sp. F7 belongs to the lipopeptide group based on the analysis of the FTIR results. The FTIR results showed the presence of C=O and N-H bonds which indicated the presence of peptide bonds as a constituent of the hydrophilic part and C=C bonds, C-H bonds which indicated the presence of a lipid structure as a constituent of the hydrophobic part of the biosurfactant. This biosurfactant is non-ionic based on the agar diffusion test and has a critical micelle concentration value of 55.16 mg/l. From the research conducted, it was found that the optimum immobilization process of Bacillus sp. F7 can be done by using Na-alginate concentration of 2.5% (w/v), CaCl2 concentration of 3.68% (w/v), hardening time of 60 minutes with an inoculum density of 106 CFU/ml which will produce a dry weight of biosurfactant around 0.16 g/l, reduced IFT to 25.15%, and produced a biosurfactant with a non-ionic type of lipopeptide. This research can be developed further by optimizing the ratio between the volume of Na-alginate solution and cell density in the immobilization process and the optimum environmental parameters in the incubation process so that the stability of beads and yields of biosurfactants can be further improved.